Gene and drug delivery system and potential treatment into inner ear for protection and regeneration - Kanzaki, Sho (Frontiers in Pharmacology, 2014)
The most common type of hearing loss results from damage to the cochlea including lost hair cells (HCs) and spiral ganglion neurons (SGNs). In mammals, cochlear HC loss causes irreversible hearing impairment because this type of sensory cell cannot regenerate. The protection of SGN degeneration has implications for cochlear implant to patients with severe deafness. This review summarizes the several treatments for HC regeneration based on experiments. We discuss how the neurotrophic factor transgene expression can protect SGN degeneration and describe potential new therapeutic interventions to reduce hearing loss. We also summarized viral vectors and introduced the gene and drug delivery system for cochlear hair cells regeneration and protection. Finally, we introduce the novel endoscopy we developed for local injection into cochlea.